The Natural Host Range Shift and Subsequent Evolution of Canine Parvovirus Resulted from Virus-Specific Binding to the Canine Transferrin Receptor - Hueffer, Karsten (American Society for Microbiology, 2003)
Canine parvovirus (CPV) is a host range variant of a feline virus that acquired the ability to infect dogs through changes in its capsid protein. Canine and feline viruses both use the feline transferrin receptor (TfR) to infect feline cells, and here we show that CPV infects canine cells through its ability to specifically bind the canine TfR. Receptor binding on host cells at 37°C only partially correlated with the host ranges of the viruses, and an intermediate virus strain (CPV type 2) bound to higher levels on cells than did either the feline panleukopenia virus or a later strain of CPV. During the process of adaptation to dogs the later variant strain of CPV gained the ability to more efficiently use the canine TfR for infection and also showed reduced binding to feline and canine cells compared to CPV type 2. Differences on the top and the side of the threefold spike of the capsid surface controlled specific TfR binding and the efficiency of binding to feline and canine cells, and these differences also determined the cell infection properties of the viruses.